The 1988 “Niagara Accord” in Perspective: The Ontario Wine Industry in Six Historical Phases - Dutil, Patrice (Ontario History)

(untitled) (The Ontario Historical Society, 2024)
The purpose of this article is to document the measures adopted in the late 1980s in response to the trade situation, to propose an understanding of the history of the winemaking industry in Ontario in six phases shaped by policy responses and to reflect on the forces of change. Were the challenges to the status quo external or internal? To what degree were changes simply incremental? Were the salient forces entrepreneurial, political, or bureaucratic? To what degree were key policy entrepreneurs important? Finally, this article examines the evolution of instrument choices that were made by the provincial government to protect and promote the winemaking industry, both as a product and as a destination.